Effects of strategic Ta'awun on sustainable, entrepreneurial and urbanised smart society in Muslim world - Mhd. Sarif, Suhaimi (ZR Resources, 2018)
This study explores the effects of strategic ta'awun on sustainable, entrepreneurial and urbanised smart society in Muslim world. Ta'awun is a Divine commandment to humanity for mutual cooperation in optimising benefits of human civilisation. It is a default for communities of practice with unified objectives in making the world a better place. The mutual cooperation driven by unified understanding provides synergy for sustainable development, entrepreneurial eco-system for economic growth and urbanised in human population, which leads to smart society. The study interviewed five key decision makers and three policy makers represented different geographical locations (Southeast Asia, South Asia, Middle East Asia, North America, and Europe). The informants argued that degree of strategic ta'awun determines the level of sustainability for entrepreneurial smart city. The dependency to major International aid such as from IMF, WHO, UNHCR, and UNESCO has reduced strategic cooperation among the society in the Muslim world. The study suggests the future research to employ case study method for more contextual insights.